2010
DOI: 10.1016/j.immuni.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Hes1 Is a Critical but Context-Dependent Mediator of Canonical Notch Signaling in Lymphocyte Development and Transformation

Abstract: Although canonical Notch signaling regulates multiple hematopoietic lineage decisions including T cell and marginal zone B cell fate specification, the downstream molecular mediators of Notch function are largely unknown. We showed here that conditional inactivation of Hes1, a well-characterized Notch target gene, in adult murine bone marrow (BM) cells severely impaired T cell development without affecting other Notch-dependent hematopoietic lineages such as marginal zone B cells. Competitive mixed BM chimeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
116
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 46 publications
12
116
1
Order By: Relevance
“…These results have further been confirmed in a different in vivo model by conditionally deleting hes1 in ICN1-induced leukemias. 17 Altogether indicates that hes1 activation is absolutely required for the maintenance of Notchdependent T-cell leukemias in vivo. Mutations in the Notch1 heterodimerization domain that give rise to ligandindependent but γ-secretase-dependent …”
Section: Resultsmentioning
confidence: 97%
“…These results have further been confirmed in a different in vivo model by conditionally deleting hes1 in ICN1-induced leukemias. 17 Altogether indicates that hes1 activation is absolutely required for the maintenance of Notchdependent T-cell leukemias in vivo. Mutations in the Notch1 heterodimerization domain that give rise to ligandindependent but γ-secretase-dependent …”
Section: Resultsmentioning
confidence: 97%
“…It has been shown that, although Hes1-deficient mice do not show clear abnormalities in their hematopoietic system, the depletion of both Hes1 and Hes5 induces overproduction of nonfunctional HSCs, in which Hes target genes such as Gata2 are abnormally up-regulated (Guiu et al, 2013). Hes1 is also reported to be an important regulator of the development of T cell acute lymphoblastic leukemia (Espinosa et al, 2010;Wendorff et al, 2010).…”
Section: Forced Expression Of Hes1 Results In Increased Numbers Of Qumentioning
confidence: 99%
“…1). Although the transcription factor HES1 was recently shown to be an important Notch mediator for T cell lineage commitment, conditional inactivation of HES1 does not lead to the accumulation of B cells or DCs in the thymus 21 . This result suggests that Notch signalling specifies the T cell lineage through the activation of additional downstream target genes.…”
Section: Developmental Roles For Notchmentioning
confidence: 98%
“…Notch signalling is highest in immature αβ T cells (including in early thymic progenitors (ETPs), double-negative 2 (DN2) thymocytes and DN3a thymocytes) up to the DN3 stage, at which cells have to pass a critical checkpoint known as β-selection 27 . In these immature thymocytes, Notch 1, but not HES1, is continuously required to restrict developing αβ T cells to the T cell lineage 21 . However, once specified, γδ T cells are less dependent on Notch signalling, at least in the mouse.…”
Section: Developmental Roles For Notchmentioning
confidence: 99%